The results of surgical treatment of patients with large and complex incisional hernias of the anterior abdominal wall in a multidisciplinary hospital - E. N. Degovtsov; P. V. Kolyadko; V. P. Kolyadko; A. V. Satinov (Бюллетень сибирской медицины)
Objectives. To evaluate the immediate results of surgical treatment of patients with large incisional hernia of the anterior abdominal wall with the use of the mesh implants.Materials and methods. The data were retrospectively collected and analyzed. The study included patients with a large and / or complex incisional hernia. There were 108 patients who underwent incisional hernia repair with mesh reinforcement in the period from 2012 to 2016. In all cases the repairs were made with mesh implants. The average age of patients was (56.4 ± 10.4) years. The body mass index (BMI) was on average (32.6 ± 6.24) kg/m2. The medial localization of the hernia was 102 (94.44%). The width of the hernia defect averaged (12.2 ± 3.7) cm. Implants were placement in onlay positions – 19 (17.6%), sublay – 49 (45.37%), IPOM (Intraperitoneal onlay mesh) – 30 (27.77%) patients, the component separation technique (CST) with mesh reinforcement was used in 10 (9.25%) patients. Active aspiration drainage was performed in 72 (66.66%) patients.Results. The average time for draining the postoperative wound was (5 ± 2.2) days. The number of wound complications was 23 (21.3%), the number of seromas of the postoperative wound prevailed was 16 (14.8%) patients, of which 2 (1.85%) were chronic abdominal wall seromas, hematoma occurred in  2 patients (1.85%), the number of prolonged serous exudation was 7 (6.5%), necrosis of the wound edges occurred in 4 (3.7%) patients. There was no mortality. Reliably more often wound complications occurred in patients with large hernia defects (p = 0.006), and also with an increase in the duration of surgical intervention (p = 0.01). The hospital-stay in patients with complications was significantly greater (p < 0.001), the need for analgesics also increased (p < 0.001).Conclusion. Prevention of wound complications after large and complex incisional hernia repair with mesh reinforcement is an important direction in improving the results of surgical treatment in this category of patients.